2019
DOI: 10.1038/s41598-019-47179-4
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Single Molecule Raman Scattering using Sprouted Potato Shaped Bimetallic Nanoparticles

Abstract: Herein, for the first time, we report the single molecule surface enhanced resonance Raman scattering (SERRS) and surface enhanced Raman scattering (SERS) spectra with high signal to noise ratio (S/N) using plasmon-active substrates fabricated by sprouted potato shaped Au-Ag bimetallic nanoparticles, prepared using a new one-step synthesis method. This particular shape of the nanoparticles has been obtained by fixing the amount of Au and carefully adjusting the amount of Ag. These nanoparticles have been chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 54 publications
2
24
0
Order By: Relevance
“…In metal nanoparticle suspensions for SERS sensing applications, it is important to control the nanoparticle aggregation and distribution. The colloidal nanoparticle solution can be directly spotted on a glass slide followed by evaporation of the solution (dropcasting) [61,62] (Figure 2a). This method is easy and fast but without specific control of the nanoparticle distributions and signal reproducibility.…”
Section: Sers Substrates Used For Biosensingmentioning
confidence: 99%
“…In metal nanoparticle suspensions for SERS sensing applications, it is important to control the nanoparticle aggregation and distribution. The colloidal nanoparticle solution can be directly spotted on a glass slide followed by evaporation of the solution (dropcasting) [61,62] (Figure 2a). This method is easy and fast but without specific control of the nanoparticle distributions and signal reproducibility.…”
Section: Sers Substrates Used For Biosensingmentioning
confidence: 99%
“…The shape of these Au/Ag nanoparticles was obtained by carefully setting the quantity of silver for a given quantity of gold. Thus, the authors obtained a LOD of 1 fM for methylene blue molecules [ 80 ]. Joseph et al reported on the fabrication AuAg@Ag hollow cubic nanosystems for a detection of mercaptothiophenol (4-MPh) molecules.…”
Section: Novelties On Plasmonic and Non-plasmonic Nanomaterials Fomentioning
confidence: 99%
“…The peak at 1640 cm −1 was due to molecular H 2 O bending vibrations [78]. The features at 2850-2950 cm −1 indicated the presence of sp 3 -hybridized C-H bonds [80]. Features in the 1000-1450 cm −1 region can be assigned to C-N and possibly C-O stretching vibrations [44,50].…”
Section: Formation and Characterization Of Cu/g-cn Materials Produced By Pulsed Laser Ablation In Acetonitrilementioning
confidence: 99%
“…Features in the 1000-1450 cm −1 region can be assigned to C-N and possibly C-O stretching vibrations [44,50]. The sharp peak at 2120 cm −1 was due to terminal C≡N bond stretching within the incompletely condensed carbon nitride matrix [79,80]. The strong Raman peak at 2155 cm −1 confirmed this assignment (Figure 5b), although it is not clear why there should be a 35 cm −1 difference between the IR and Raman data.…”
Section: Formation and Characterization Of Cu/g-cn Materials Produced By Pulsed Laser Ablation In Acetonitrilementioning
confidence: 99%